Analisis Peran Lembaga Amil Zakat Sebagai Agen Distribusi (Studi Kasus Lembaga Amil Zakat Rumah Zakat Cabang Malang) - Nisak, Khoirun; Burhan, M. Umar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Zakat obligation is present in order that humans are being able to help each other and justice distribution is created among civilians. Zakat has strong potency to builds up the welfare when it is managed properly, it should be paid to the agency of amil zakat and the institution of amil zakat so the zakat can be utilized and distributed to the mustahik through some productive programs. The very aim of it is the funds coming from zakat will not run out only through consumption at once. Therefore the main goal, transformation from mustahik for being muzakki can be achieved. Keywords: zakat, distribution, the institution of amil zakat